USING ONLINE GRAMMAR CHECKER TO IMPROVE GRADE TEN STUDENTS’ WRITING ACHIEVEMENT AND WRITING QUALITY - Tasniima Melatifajri Samboja; Susana Teopilus; Alberik Ryan Tendy Wijaya (Widya Mandala Surabaya Catholic University, 2024)
Writing is a way to express one’s ideas. Good writing is important to uphold various aspects of life, including education, work, and social interaction. However, writing is considered a difficult skill by students. This research aims to find out whether students’ writing achievement and writing quality can be improved using the Grammarly application, which was proved by the data collected from the pre-test and post-test. The study used a pre-experimental method. The research subjects were grade ten students of a private high school in Surabaya. It showed that there was a significant difference in the writing achievements. The data showed that the mean of the pre-test was 82.641, the N was 32. The mean score of the post-test was 87.203. This study reveals that Grammarly has been proven effective in improving students' writing quality in terms of the three writing aspects, namely vocabulary, mechanics, and language use.